PERSPECTIVES ON ADDING NEW LETTERS TO GENETIC ALPHABET - Alghannam, Lamia (International Journal of Current Pharmaceutical Research, 2016)
Objective: Today, DNA-based technologies are limited in the range, efficiency and accuracy of their application by the four bases in the structure of DNA. Development of DNA molecules with a higher number of bases could contribute to the resolution of the problem. Moreover, the addition of new letters to the genetic alphabet could be used for the treatment of disorders and development of DNA molecules with extended functionality. The aim of the research was to analyse the current abilities and future perspectives of expanded alphabet with respect to the mentioned problems. Methods: The research questions were addressed by the research of the articles present in NCBI and Google Scholar databases. With the application of developed key terms, such as expanded gene codeâ€, expanded genetic alphabetâ€ and genetic alphabet and medicineâ€, and certain inclusion and exclusion criteria, six articles published between 2006 and 2016 were selected for analysis. Results: It was identified that most of the applications of DNA with six letters possible for today use are associated with the expansion in the functional abilities of the modern DNA-based methods. Some of the researchers show the higher binding ability and affinity of the artificial DNA aptamers and suggest their application for treatment and increased functions of DNA. However, still a great number of other applications are suggested for the future. They include the production of proteins and enzymes with new qualities, making DNA molecule a molecular probe for tumour detection and a number of other applications. Conclusion: Addition of new letters to the genetic alphabet can be a powerful tool for improvement of diagnostic technologies used today. However, more research in this field is still needed for wider application and development of new treatment approaches.